(3GdhXjaI GdQbGHjI deMceI YOd GdGJMGO GdChQhHi ddCYeGd GdbGfhfjI GdUGOQI Yf GdeLdS h GddLfI (B: s (3GdQbGHI GddGMbI (B/ s - (3EOQjS OejG chQjQGs; (3eMeO SGeM YeQh s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3jJfGhd gPG GdHMK OhQ eMceI YOd GdGJMGO GdChQhHi ai QbGHI GdCYeGd GdbGfhfjI GdUGOQI Yf GdeLdS(B: (3h GddLfI(B: (3h Pdc ai GNJUGUGJgG GdbVGFjI(B: (3h JYJHQ GdeMceI ef Cge GdeDSSGJ ai GdGJMGO GdChQhHi GdJi JdYH OhQG HGQRG ai JOYje SjGOI GdbGfhf(B: (3h EQSGA GdeHGOF GdJi JSge ai YedjI GdEfOeGL GdChQhHi(B. (3h JJeKd GdGYeGd GdbGfhfjI GdUGOQI Yf GdeLdS(B: (3h GddLfI ai GddhGFM(B: (3h GdJhLjgGJ(B: (3h GdbQGQGJ(B: (3h GdJhUjGJ(B: (3h GdBQGA(B: (3h CjVG JUOQ GddLfI HYV GdCYeGd ZjQ GdefUhU YdjgG ai eYGgOI JSjjQ GdGJMGO GdChQhHi(B. (3h JJeKd GdCYeGd GdbGfhfjI GdUGOQI Yf GdeLdS(B: (3h GddLfI ai GddhGFM(B: (3h GdJhLgjGJ(B: (3h GdbQGQGJ(B: (3h GdJhUjGJ(B: (3h GdCQGA(B: (3h CjVG JUOQ GddLfI HYV GdCYeGd ZjQ GdefUhU YdjgG ai eYGgOI JSjjQ GdGJMGO GdChQhHi (B((3Ji Ea Ej jh(B): (3dEKGQI ehVhY eYjf ddfbGT(B: (3eKdG(B: (3GdChQGb GdHjVGA h GdNVQGA(B. (3h JQGbH GdeMceI TQYjI GdCYeGd GdbGfhfjI GdUGOQI Yf GdeLdS h GddLfI(B: (3h gi(B: (3GdbQGQGJ(B: (3h GddhGFM(B: (3h GdJhLjgGJ(B: (3h dG JfWhi GdQbGHI Ydi GdJhUjGJ h GdCQGA; dYOe EdRGejJgG EdG EPG fUJ GdeYGgOI Ydi GdRGejI UOhQ JhUjI bHd GJNGP bQGQ eG s
(3jTJed Ydi edGMb(B: (3UaMI (B212-261s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi , (B2019s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B262-268s
Keywords: (3GdbGfhf GdOhdjs; (3GdGJMGO GdChQhHis; (3GdCYeGd GdbGfhfjIs; (3GdhXjaI GdQbGHjIs; (3GdGfOeGL GdGhQhHi s; (3GdGJMGO GdGhQhHi s; (3GdWYf GdeHGTQs; (3GdeMceg GdhWfjgs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs